Anaesthetic Management in Scoliosis Surgery in a Patient with Fontan Circulation - Oliveira, Flávia; Dias, José (Journal of the Portuguese Society of Anesthesiology, 2019)
The anesthetic management of patients with Fontan physiology can become very complex, particularly in invasive non-cardiac surgeries, such as surgery to scoliosis. The aim of the present study is to revisit the Fontan physiology and to systematize some behaviors and important choices that must be taken in the anesthesia of these patients. It is important to maintain adequate preload, hemodynamic stability and prevention of elevated pulmonary vascular resistance in these patients to allow for an effective pulmonary perfusion.